Formation of resistance of Candida fungi to fungicidal drugs - HrynzovskaAnastasіia; Bobyr , Vitaly (The Ukrainian Scientific Medical Youth Journal, 2024)
the work is devoted to the study of the sensitivity of fungi of the Candida genus to the main fungicides and to the investigation of the possibility of artificially forming the resistance of microorganisms - the causative agents of human fungal infections to these drugs. It has been experimentally proven that the sensitivity of fungi of the genus Candida to the main groups of fungicides depends on the species and strain characteristics of microorganisms. In particular, clinical strains of C. albicans were shown to be most sensitive to the 1,2,4 triazole propiconazole and most resistant to prochlorase, clinical strains of C. krusei and C. glabrata had the highest susceptibility to tebuconazole, while clinical strains of C. krusei also showed the highest resistance to prochlorase in contrast to C. glabrata, which had the highest resistance to flutriafol. The peculiarities of the formation of fungicide resistance in representatives of the genus Candida are substantiated, and it is shown that this process depends both on the strain and species characteristics of microscopic fungi, and on the chemical structure of the drugs. In particular, it was established that C. krusei quickly develops resistance to all compounds except prochloraz, while C. glabrata acquires significant resistance to the triazoles tebuconazole and propiconazole, and C. albicans to imazalil. Features of the dynamics of the formation of resistance to fungicides in various species of Candida spp. In particular, in C. albicans strains, a significant decrease in sensitivity was often observed after one or two passages of culture, followed by a significant "sensitization" of the strain to the fungicide for at least two passages. In addition, it is shown that the process of adaptation of candida to fungicides can be accompanied by the slowing down of culture growth at 7-10 passages and the intensification of the phenomenon of bacterial dissociation with the appearance of atypical colonies of smaller sizes, translucent and with a viscous consistency. It is shown that, unlike C. krusei, the process of culture adaptation to C. albicans and C. glabrata fungicides is accompanied by population "depletion", which is manifested by a slowdown in its growth.